PENERAPAN MODEL PEMBELAJARAN COOPERATIVE SCRIPT DENGAN BANTUAN MEDIA AUDIO VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IVC SD NEGERI 188 PEKANBARU - Srikandi Setia Ningsih T; Zariul Antosa; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to improve social learning outcomes with Cooperative Script learning model with the help of audio visual media in the students of IVC SDN 188 Pekanbaru. This study is classroom action research (CAR), with the subject of research was student class IVC SDN 188 Pekanbaru. The result of research showed that social learning through cooperative script model with the help of audio visual media can improve social learning outcomes. This can be seen from : (1) teacher activity increases from percentage of teacher activity in the first cycle of 66,66% (enough category), in the second cycles of 91,67% (very good category); (2) student learning activities of increase in each cycle. Student learning activities increased from the percentage of student learning activities in the first cycle of 62,50% (enough category), on the second cycles of 87,50% (very good category); (3) student learning outcomes increase from average value before action equal to 63,00 with completness 43,33% (unfinished), increase in cycles I equal to 12,95% with a value 71,16, and in cycle II increased by 28,03% with value 80,66. With that, the conclusion is implementation of cooperative script learning model with the help of audio visual media can improve social learning outcomes.Keywords : Cooperative Script learning model with the help of audio visual media, learningoutcomes, Classroom Action Research (CAR).